A case of two inversion (10) recombinants in a family. Issue 7 (July 1989) - Roberts, P; Williams, J; Sills, M A
Abstract : A family is described in which the mother's four pregnancies resulted in one spontaneous abortion, one healthy boy, and a male and female sib with developmental delay and multiple minor dysmorphic features. Chromosome analysis showed a large pericentric inversion of chromosome 10, involving the region between bands p15.1 and q25.2, in the father and the healthy son: 46, XY, inv(10) (p15.1q25.2), and an unbalanced karyotype in the two affected sibs: rec(10), dup p, inv(10) (p15.1q25.2). The unbalanced chromosome has been produced by meiotic recombination between the inversion chromosome and its normal homologue. The two affected sibs have partial duplication of 10p and partial deficiency of 10q, and share a large number of clinical features, several of which have previously been described in both of these chromosome imbalances. We believe this to be the largest pericentric inversion of chromosome 10 reported to have produced recombinant offspring.